Determining the suitability of mass spectrometry for understanding the dissolution processes involved with pharmaceutical tablets - Lewis, C.; Ray, A.; Bristow, T.; Wren, S. (Wiley, 2015)
RATIONALE: A current challenge for analytical chemists is the development of measurement systems and approaches required to understand dynamic processes such as tablet dissolution. The design and development of oral tablets could be improved by the availability of detailed information about the rates of release of the individual tablet components. Small footprint mass spectrometry (MS) systems are gaining use for on-line reaction monitoring because of their ability to rapidly determine multiple reactant, intermediate, and product species. We have therefore assessed the utility of such MS systems to the study of dissolution processes.